Potensi Kadar Nira dan Produksi Beberapa Varietas Sorgum Manis (Sorghum vulgare) di Lahan Kering Area Hutan sebagai Bahan Baku Bioetanol - Praptiningsih Gamawati Adinurani; Sri Rahayu; Luluk Sulistiyo Budi (Universitas Merdeka Madiun, 2019)
Sweet sorghum is one of the bioethanol producing plants that can be cultivated on dry land with a wide climate range. The study aims to utilize dry land forest areas for the development of several varieties of sweet sorghum as a bioethanol feedstock. The types used are Suri 3, Kawali, Super 2 and Suri 4 varieties which cultivated at various biofertilizer doses per plant, namely 5 g, 10 g, and 15 g. This experiments used Randomized Block Designed factorial followed by Duncan's Multiple Range Test. The results showed that the Suri 3, Kawali and Super 2 varieties had above-average agronomic and production characters with the highest values at stem height (301.28 cm), stem weight (145.21g), and seed dry weight (39.74 g) achieved by the variety of Super 2.Â Varieties of Suri 3Â has the highest potential the content of sugar in the stem (16.69%). Suri 4 variety produces the most volume of juice with the lowest of sugar content. The interaction of varietiesÂ and biofertilizer doses was significantly different against the number of nodules, and the highest of nodules number accomplished by Super 2 varieties at a dose of 10 g (11.77).